Comment on 'A scattering quantum circuit for measuring Bell's time inequality: a nuclear magnetic resonance demonstration using maximally mixed states' - Knee, G; Gauger, E; Briggs, G; Benjamin, S (IOP Publishing, 2012)
A recent paper by Souza, Oliveira and Sarthour (SOS) reports the experimental violation of a Leggett–Garg (LG) inequality (sometimes referred to as a temporal Bell inequality). The inequality tests for quantum mechanical superposition: if the inequality is violated, the dynamics cannot be explained by a large class of classical theories under the heading of macrorealism. Experimental tests of the LG inequality are beset by the difficulty of carrying out the necessary so-called 'non-invasive' measurements (which for the macrorealist will extract information from a system of interest without disturbing it). SOS argue that they nevertheless achieve this difficult goal by putting the system in a maximally mixed state. The system then allegedly undergoes no perturbation during their experiment. Unfortunately, the method is ultimately unconvincing to a skeptical macrorealist and so the conclusions drawn by SOS are unjustified.